A high-intensity focused ultrasound surgery theater design in a private clinic - Lian Zhang; Felix Wu Shun Wong (Wolters Kluwer Medknow Publications, 2020)
Noninvasive high-intensity focused ultrasound (HIFU) surgery has become a popular surgical treatment for fibroids, adenomyosis, and various gynecological diseases in China and many countries. While traditional theater designs in hospitals are standardized and easily available for reference, an outpatient HIFU theater design is not yet available in the literature or is nonexistent. The authors presented the design and setup of an ultrasound-guided HIFU center in Hong Kong and listed the space and safety requirements and special features of their HIFU theater. Despite its limited space, the HIFU surgery center has made available a nursing station, a changing room, and an observation/recovery room. A room for learning HIFU treatment and viewing is also available without any intrusion of patient's privacy during treatment. The article concluded that because the space requirements for a HIFU theater were much reduced, the cost of the HIFU theater setup would be much cost-effective. Finally, its relaxing lighting environment was totally different and impossible to be installed in a traditional operating theater in a hospital.